2010
DOI: 10.1785/0120100057
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Ground-Motion Simulation Using a Hybrid Approach

Abstract: This paper describes refinements to the hybrid broadband ground motion simulation methodology of Graves and Pitarka (2004), which combines a deterministic approach at low frequencies (f < 1 Hz) with a semi-stochastic approach at high frequencies (f > 1 Hz). In our approach, fault rupture is represented kinematically and incorporates spatial heterogeneity in slip, rupture speed and rise time. The prescribed slip distribution is constrained to follow an inverse wavenumber-squared falloff and the average rupture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
436
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(445 citation statements)
references
References 74 publications
6
436
1
2
Order By: Relevance
“…We calculated the stressdrop distributions following Ripperger and Mai (2004). Rise times of subfaults were assumed to be proportional to the square root of slip by constraining the fault average rise-time value with empirical scalings (Graves and Pitarka, 2010):…”
Section: Strong-motion Simulations Strong-motion Simulation Methods Anmentioning
confidence: 99%
“…We calculated the stressdrop distributions following Ripperger and Mai (2004). Rise times of subfaults were assumed to be proportional to the square root of slip by constraining the fault average rise-time value with empirical scalings (Graves and Pitarka, 2010):…”
Section: Strong-motion Simulations Strong-motion Simulation Methods Anmentioning
confidence: 99%
“…The summation in the seismic demand hazard, as given by Equation (6), is considered over the ! IM levels for which ground motions are selected.…”
Section: Non-parametric Computationmentioning
confidence: 99%
“…(!"#|!") parametrically represented continuously over the range of IM levels considered (as well as reasonable amount of extrapolation), Equation (6) can be evaluated via summation over a large number of IM values, allowing for a more accurate representation of the derivate of the hazard curve (!! !"…”
Section: Parametric Computationmentioning
confidence: 99%
“…important source information on the main causes affecting the strong ground motion behavior. Most previous studies adopted 3D simulation approaches to estimate long-period ground motions (e.g., Kamae et al 1998;Furumura et al 2002;Graves and Pitarka 2010). In addition, Lee et al (2014) showed that their model explained long-period ground motions well, so we also tried to estimate the long-period ground motions following the source rupture model derived by Lee et al (2014).…”
Section: Application Of Broadband Waveformsmentioning
confidence: 99%